Longitudinal association between caesarean section birth and cardio‐vascular risk profiles among adolescents in Australia. (4th August 2022) - Begum, Tahmina; Fatima, Yaqoot; Anuradha, Satyamurthy; Hasan, Md; Mamun, Abdullah Al
Abstract: Objective : To examine the association of cesarean section (C‐section) with cardiovascular disease (CVD) risk biomarkers among Australian children. Methods : The Longitudinal Study of Australian Children (LSAC) birth cohort was prospectively followed for body mass index (BMI) trajectory, and then linked with CVD risk indicators of children; waist circumference (WC), systolic blood pressure (SBP), blood glucose, high‐density lipoprotein (HDL), triglyceride (TG), fat mass index (FMI) and composite metabolic syndrome (CMetS) score. Multivariable linear regression analysis was done to assess the association of C‐sections with CVD risk biomarkers. Results : Of 1, 874 study children, 30% had C‐sections; the mean age (SD) was 11.50 (0.50) years, and 49% were female. Against the vaginally‐born cohort, Caesarean‐born children showed a higher Z‐ score for five of the seven CVD risk indicators in regression analysis; WC (0.15; p=0.003), SBP (0.16; p=0.003), inverse HDL (0.15; p=0.003), FMI (0.12; p=0.004), and CMetS (0.45; p=0.004) score. Children with accelerated BMI trajectory had higher CMetS scores for both the delivery types while the C‐section cohort showed statistical association only (1.69; p=0.006) Conclusion : C‐section was independently associated with increased CVD risk profiles of children, further increased with high BMI trajectory. Implication for public health : The chronic disease risk of C‐sections should be discussed with families to reduce clinically unrequired C‐sections.